Exploring Mixed Interaction Mode in Virtual Reality: Controller-based and Hand Gesture Integration - Lee, Yemon (Auckland University of Technology, 2024)
This research addresses the challenge of designing intuitive and effective interaction modes for object manipulation tasks in virtual reality (VR). Traditional VR interactions heavily rely on controller-based mode, which may not provide the most natural or immersive experience. In contrast, hand gesture interaction mode, enabled by technologies such as Leap Motion, offer a more natural means of interaction but often lack the precision of controller-based interaction mode. This situation opens up an opportunity to design VR interactions that seamlessly blend naturalness with precision. This research therefore explores the benefits of a mixed interaction mode that combines the controller-based interaction mode with the hand gesture interaction mode, unlocking new possibilities for innovative and intuitive Human-Computer Interaction (HCI) in VR. The study was conducted in two phases, considering both the application scenario and the target user groups. In the first phase, 40 participants evaluated the effectiveness of the mixed interaction mode in a puzzle-solving setting. Task completion times were analysed, and participant feedback was collected to assess the combination of the controller-based and hand gesture interaction modes. Based on these findings, a second phase study was conducted in a cockpit setting to further refine the initial observations and explore the applicability and performance of the combined input approach in a specific context. A mixed-methods analysis was conducted to evaluate the controller-based, hand gesture, and mixed interaction modes for each interaction task. The findings indicate that while the mixed interaction mode enhances the user experience, it also introduces certain challenges. Insights into VR object manipulation design guidelines were generated, suggesting that the controller-based and hand gesture interaction modes each have distinct strengths and weaknesses. The optimal interaction mode depends on the task as well as the user’s experience and skill level. Further research is needed to explore the limitations and potential improvements of the mixed interaction mode, particularly in more complex tasks. This research expands the knowledge of VR object manipulation design by summarising the suitability of interaction tasks in virtual environments. It also offers design guidelines for VR designers, enabling informed decisions when designing object manipulation tasks, and has implications for future studies in the field of VR interaction modes and user experience.